Rh(III)‐Catalyzed Regioselective Acetylation of sp2 C−H Bond Starting from Paraformaldehyde. Issue 16 (20th February 2019) - Wan, Ting; Du, Sidong; Pi, Chao; Wang, Yong; Li, Rongbin; Wu, Yangjie; Cui, Xiuling
Abstract: Rh(III)‐catalyzed acetylation of sp 2 C−H bonds has been realized using paraformaldehyde as an acetylating reagent. This procedure features simultaneous formation of two C−C bonds, external oxidants free, and water as the sole byproducts, thus offering an environmentally benign acetylation of arenes. A range of functional groups tolerance were observed. Abstract : Ride the rhodacycle : Rh(III)‐catalyzed regioselective acetylation of arenes using paraformaldehyde as a novel acetyl reagent, which may undergo twice insertion of aldehyde and form two C−C bonds in one‐pot manner. This protocol proceeded smoothly under air atmosphere, avoided external oxidants, and produced water as the sole byproduct.